An Overview of the Effectiveness of the Most Important Native Medicinal Plants of Iran on Hemorrhoid Based on Iranian Traditional Medicine Textbooks - Mahnaz Mardani (Journal of Global Pharma Technology, 2016)
Hemorrhoid diseaseoccursfollowing the blood-filling of vascular structures of submucosal networks in the anal area. Patients usually feel no painsand the symptoms include a feeling of rectal congestion, mucus secretion, and bright red blood dripping. Surgical treatment is of the most common treatment methods of hemorrhoid. In addition to the usual treatments, classic therapies and complementary medicine are also applied. Medicinal herbs have been traditionally a source for the treatment of many diseases. Many native medicinal plants of Iran have had effective properties on hemorrhoid. Thus, in this review,the effective medicinal plants of Iranian ethnobotanical resources on hemorrhoid were reported. In this review study, a search for articles by the keywords hemorrhoid,ethnobotanical, and medicinal plants was done. A search on the databases, such as Scopus, ISI C, S ID, MegIran,and a number of other databases was performed. Based on the results obtained, 11 herbs from different parts of Iran are traditionally used to treat anorexia. Such medicinal plants as pistachio from mountainous trees, yarrow, camel thorn, etc. are of the effective herbs on hemorrhoid.Keywords: gastrointestinal tract, Hemorrhoid, Medicinal herb, Iranian ethnobotany.